Acquisition and generative responding following print‐to‐braille construction response training with sighted learners. Issue 1 (24th October 2018) - Lillie, Madelynn A.; Tiger, Jeffrey H.
Abstract : Previous researchers have taught sighted adults to match braille sample stimuli to print comparisons in a matching‐to‐sample (MTS) format and assessed the emergence of other braille repertoires, such as transcribing and reading braille following this training. Although participants learned to match to sample with braille, they displayed limited emergence of other braille repertoires. Lack of generative responding may have resulted from participants' over‐selective attending to components of compound braille characters during instruction. We taught undergraduates to construct braille characters given a print sample, which required attending to each individual braille symbol, and assessed generative braille responding. Participants met mastery of 378 braille construction responses and demonstrated modestly improved responding compared with previous research.